Antioxidant graphite material and preparation method thereof

By mixing boron-containing ester compounds with coal asphalt and coke aggregate, heating and cold isostatic pressure treatment, and graphitization is combined with the existing graphite production process, the problems of process complexity and high cost in improving graphite oxidation resistance are solved, and the degree of graphitization and oxidation resistance are improved are improved.

CN119528576APending Publication Date: 2025-02-28GANNAN NORMAL UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411717684.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

In improving graphite oxidation resistance, the prior art has problems such as complex process, high cost, and mismatch between the silicon C coating and graphite thermal expansion coefficient. The inhibitory effect of phosphorus is mainly reflected in the surface of the material, which is easily worn or corroded.

Method used

The ester compounds containing boron elements are mixed with the binder coal asphalt, and heated and kneaded with coke aggregate to form a paste material. After cooling, powdering, isostatic molding, roasting and graphitization are carried out. The entire technical route is the same as the process of large-scale graphite production by enterprises.

Benefits of technology

By adding boron-containing solvents, the degree of graphitization and oxidation resistance can be improved, and this method can be directly combined with the existing production process without increasing the process and production costs. Boron element is distributed in the body phase of graphite, reducing the number of carbon active points and reactivity, manifested as an intrinsic oxidation inhibitor, and is not affected by wear or corrosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528576A_ABST
    Figure CN119528576A_ABST
Patent Text Reader

Abstract

The invention provides an antioxidant graphite material and a preparation method thereof. The preparation method of the anti-oxidation graphite material comprises the following steps: mixing an ester compound containing a boron element with a binder coal pitch, heating and kneading the mixture and coke aggregate (pitch coke or petroleum coke) to form a pasty material, cooling the pasty material, preparing pressed powder, performing isostatic compaction, roasting and graphitizing to obtain the anti-oxidation graphite material. The whole technical route is the same as a large-scale graphite production process of an enterprise and can be directly combined with an existing production process, and the aim of improving the graphitization degree so as to improve the oxidation resistance of the graphite can be achieved without increasing procedures and production cost. Boron and boron in the boron-containing solvent can be distributed in the bulk phase of graphite and reduce the number and reaction activity of carbon active sites, so that the boron-containing solvent is an intrinsic oxidation inhibitor, and the inhibition effect of the bulk phase cannot be affected even if surface loss is caused by abrasion or corrosion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of graphite materials, and in particular to an anti-oxidation graphite material and a preparation method thereof. Background Art

[0002] Graphite is widely used in nuclear energy, semiconductors, new energy and national defense. Improving the antioxidant properties of graphite is a key issue that needs to be solved in the application of graphite. There are many ways to improve the antioxidant properties of graphite, such as increasing the degree of graphitization, protecting or modifying graphite, such as impregnation, coating or doping. By impregnating phosphates, etc., a protective film is formed on the surface or pores of graphite to achieve the purpose of antioxidant; the coating method can effectively prevent the oxidation of graphite, but there are still some problems, such as SiC coating has the disadvantages of complex process, high cost, and mismatch with the thermal expansion coefficient of graphite. The most promising antioxidant method is to improve the intrinsic antioxidant properties of carbon materials by doping with chemical elements. Currently known chemical elements that can be used as effective inhibitors include phosphorus, silicon, and halogens. However, the inhibitory effect of phosphorus is mainly reflected on the surface of the material, which is easily worn or corroded.

[0003] Based on the defects of the current methods for improving the oxidation resistance of graphite, it is necessary to improve them. Summary of the invention

[0004] In view of this, the present invention provides a method for preparing an antioxidant graphite material, which comprises mixing an ester compound containing a boron element with a binder coal tar, and then heating and kneading the mixture with a coke aggregate (i.e., asphalt coke or petroleum coke) to form a paste-like material, and preparing pressed powder, isostatic pressing, roasting and graphitization after cooling. The entire technical route is the same as the process for large-scale production of graphite by an enterprise, and has the advantage that it can be directly combined with the existing production process, and the purpose of increasing the degree of graphitization and thus improving the antioxidant properties of graphite can be achieved without increasing the process and production cost.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] The present invention provides a method for preparing an oxidation-resistant graphite material, comprising the following steps:

[0007] Mixing asphalt coke or petroleum coke, coal tar, and a boron-containing solvent to obtain a mixture;

[0008] The mixture is kneaded hot, cooled, and crushed;

[0009] The crushed mixture is subjected to cold isostatic pressing;

[0010] The cold isostatically pressed mixed material is subjected to a first carbonization treatment;

[0011] The mixture that has undergone the first carbonization treatment is added into the melted asphalt for impregnation treatment;

[0012] Carrying out a second carbonization treatment on the impregnated mixture;

[0013] The mixed material subjected to the second carbonization treatment is graphitized;

[0014] Wherein, the boron-containing solvent is an ester compound containing boron element.

[0015] Preferably, the boron-containing solvent includes at least one of triisopropyl borate, triethyl borate and methyl borate.

[0016] Preferably, the particle size of the asphalt coke or petroleum coke is 3 to 30 μm;

[0017] And / or, in the step of mixing asphalt coke or petroleum coke, coal tar pitch and boron-containing solvent, the mass of coal tar pitch is 25% to 35% of the mass of asphalt coke or petroleum coke, and the mass of boron-containing solvent is 0.5 to 10% of the mass of coal tar pitch.

[0018] Preferably, the mixture is heat-kneaded at 200-250° C. for 3-5 hours, cooled, and crushed to an average particle size of 60-80 μm.

[0019] Preferably, the crushed mixture is subjected to cold isostatic pressing, wherein the process parameters of the cold isostatic pressing are: pressure of 120-140 MPa and time of 0.5-4 h.

[0020] Preferably, the cold isostatically pressed mixture is subjected to a first carbonization treatment, wherein the first carbonization treatment specifically comprises: keeping the cold isostatically pressed mixture at 1200-1300° C. for 20-100 hours under an inert atmosphere.

[0021] Preferably, the mixture that has undergone the first carbonization treatment is added to the melted asphalt for an impregnation treatment step; the impregnation treatment is specifically, adding the mixture that has undergone the first carbonization treatment to the asphalt for an impregnation treatment at 280-320° C. and 1.5-2 MPa for 2-6 hours;

[0022] Preferably, in the step of subjecting the impregnated mixture to a second carbonization treatment, the second carbonization treatment specifically comprises: keeping the impregnated mixture at 1200-1300° C. for 20-100 hours under an inert atmosphere;

[0023] The inert atmosphere includes at least one of nitrogen, helium, neon and argon.

[0024] Preferably, the graphitization treatment is specifically: graphitization treatment at 2000-2400° C. for 3-5 hours under an inert atmosphere.

[0025] In a second aspect, the present invention further provides an oxidation-resistant graphite material prepared by the preparation method.

[0026] The method for preparing an oxidation-resistant graphite material of the present invention has the following beneficial effects compared with the prior art:

[0027] The preparation method of the antioxidant graphite material of the present invention is to mix the ester compound containing the boron element with the binder coal tar, and then heat and knead with the coke aggregate (i.e., asphalt coke or petroleum coke) to form a paste material, and prepare the pressed powder, isostatic pressing, roasting and graphitization after cooling. The whole technical route is the same as the process of large-scale production of graphite in enterprises. The advantage is that it can be directly combined with the existing production process, and the purpose of increasing the degree of graphitization and thus improving the anti-oxidation of graphite can be achieved without increasing the process and production cost. Boron in the boron-containing solvent can be distributed in the bulk phase of graphite and reduce the number and reaction activity of carbon active points at the same time, thereby showing an intrinsic oxidation inhibitor, and even the surface loss caused by wear or corrosion will not affect the inhibitory effect of this bulk phase. The antioxidant graphite material prepared by the present invention is improved in its degree of graphitization and oxidation resistance by adding a boron-containing solvent compared to the one without adding a boron-containing solvent. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art descriptions. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0029] Figure 1 is the XRD pattern of the graphite material prepared in Example 1;

[0030] Figure 2 is the XRD pattern of the graphite material prepared in Example 2;

[0031] Figure 3 is the XRD pattern of the graphite material prepared in Example 3;

[0032] Figure 4 This is the XRD pattern of the graphite material prepared in Comparative Example 1. DETAILED DESCRIPTION

[0033] To make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them.

[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of the embodiments. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may be in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single values ​​within the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the numbered ranges, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated in this article, it is meant to include any quoted numbers (fractions or integers) within the indicated range.

[0036] The present invention provides a method for preparing an oxidation-resistant graphite material, comprising the following steps:

[0037] S1. Mixing asphalt coke or petroleum coke, coal tar, and a boron-containing solvent to obtain a mixture;

[0038] S2, cooling the mixture after hot kneading and crushing;

[0039] S3, subjecting the crushed mixed material to cold isostatic pressing;

[0040] S4, subjecting the cold isostatic pressing treated mixed material to a first carbonization treatment;

[0041] S5, adding the mixture that has undergone the first carbonization treatment into the melted asphalt for impregnation treatment;

[0042] S6, subjecting the impregnated mixture to a second carbonization treatment;

[0043] S7, graphitizing the mixture that has undergone the second carbonization treatment;

[0044] Wherein, the boron-containing solvent is an ester compound containing boron element.

[0045] The preparation method of the antioxidant graphite material of the present invention is to mix the ester compound containing the boron element with the binder coal tar, and then heat and knead with the coke aggregate (i.e., asphalt coke or petroleum coke) to form a paste material, and prepare the pressed powder, isostatic pressing, roasting and graphitization after cooling. The whole technical route is the same as the process of large-scale production of graphite in enterprises. The advantage is that it can be directly combined with the existing production process, and the purpose of increasing the degree of graphitization and thus improving the anti-oxidation of graphite can be achieved without increasing the process and production cost. Boron in the boron-containing solvent can be distributed in the bulk phase of graphite and reduce the number and reaction activity of carbon active points at the same time, thereby showing an intrinsic oxidation inhibitor, and even the surface loss caused by wear or corrosion will not affect the inhibitory effect of this bulk phase. The antioxidant graphite material prepared by the present invention is improved in its degree of graphitization and oxidation resistance by adding a boron-containing solvent compared to the one without adding a boron-containing solvent.

[0046] In some embodiments, the boron-containing solvent includes at least one of triisopropyl borate, triethyl borate, and methyl borate. The boron-containing solvent of the present invention is a boron-containing ester solvent that is easy to mix evenly with asphalt; and compared with boric acid, boron-containing ester solvents are less likely to destroy the structure of asphalt, after all, boric acid is a weak acid substance.

[0047] In some embodiments, the particle size of the asphalt coke or petroleum coke is 3 to 30 μm;

[0048] In some embodiments, in the step of mixing asphalt coke or petroleum coke, coal tar pitch, and a boron-containing solvent, the mass of the coal tar pitch is 25% to 35% of the mass of the asphalt coke or petroleum coke, and the mass of the boron-containing solvent is 0.5 to 10% of the mass of the coal tar pitch.

[0049] In some embodiments, the mass ratio of the boron-containing solvent to the coal tar pitch is (0.5-3):(97-99.5).

[0050] In some embodiments, the mixture is heat-kneaded at 200-250° C. for 3-5 hours, cooled, and crushed to an average particle size of 60-80 μm.

[0051] In some embodiments, the crushed mixture is subjected to cold isostatic pressing, wherein the process parameters of the cold isostatic pressing are: pressure of 120-140 MPa and time of 0.5-4 h.

[0052] In some embodiments, the cold isostatically pressed mixture is subjected to a first carbonization treatment, wherein the first carbonization treatment specifically comprises: keeping the cold isostatically pressed mixture at 1200-1300° C. for 20-100 hours under an inert atmosphere.

[0053] In some embodiments, the mixture that has undergone the first carbonization treatment is added to melted asphalt for an impregnation step; the impregnation treatment is specifically, the mixture that has undergone the first carbonization treatment is added to asphalt and impregnated for 2 to 6 hours at 280 to 320°C and 1.5 to 2 MPa.

[0054] Specifically, in the above embodiment, the mixture that has undergone the first carbonization treatment is impregnated with melted asphalt as an impregnating agent.

[0055] In some embodiments, in the step of subjecting the impregnated mixture to a second carbonization treatment, the second carbonization treatment is specifically: the impregnated mixture is kept at 1200-1300° C. for 20-100 hours under an inert atmosphere.

[0056] In some embodiments, the inert atmosphere includes at least one of nitrogen, helium, neon, and argon.

[0057] In some embodiments, the graphitization treatment is specifically: graphitization treatment at 2000-2400° C. for 3-5 hours under an inert atmosphere.

[0058] The following further illustrates the preparation method of the anti-oxidation graphite material of the present application with specific examples. This section further illustrates the content of the present invention in conjunction with specific examples, but should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0059] In the following examples and comparative examples, the pitch coke is calcined pitch coke of China Baowu Steel Group Co., Ltd., with an average particle size of 30 μm; the softening point of coal tar is 106.7° C., the coking value is 56.2%, the ash content (mass content) is 0.15%, the quinoline insoluble content (mass content) is 10%, the resin content (mass content) is 22%; and the sulfur content (mass content) is 0.2%.

[0060] Example 1

[0061] The present invention provides a method for preparing an oxidation-resistant graphite material, comprising the following steps:

[0062] S1, mixing asphalt coke, coal tar pitch and boron-containing solvent to obtain a mixture; S2, hot kneading the mixture, cooling it, and crushing it;

[0063] S3, subjecting the crushed mixed material to cold isostatic pressing;

[0064] S4, subjecting the cold isostatic pressing treated mixed material to a first carbonization treatment;

[0065] S5, adding the mixture that has undergone the first carbonization treatment into the melted asphalt for impregnation treatment;

[0066] S6, subjecting the impregnated mixture to a second carbonization treatment;

[0067] S7, graphitizing the mixture that has undergone the second carbonization treatment;

[0068] Wherein, the boron-containing solvent is triisopropyl borate;

[0069] The particle size of pitch coke is 20 μm;

[0070] In the step of mixing asphalt coke, coal tar pitch and boron-containing solvent, the mass of coal tar pitch is 30% of the mass of asphalt coke, and the mass ratio of boron-containing solvent to asphalt is 0.5:99.5;

[0071] The mixture was kneaded at 220°C for 3 h, cooled, and crushed to an average particle size of 70 μm.

[0072] The process parameters of cold isostatic pressing are: pressure 130Mpa, time 2h;

[0073] The first carbonization treatment is as follows: the cold isostatically pressed mixture is kept at 1250°C for 50 h under an argon atmosphere;

[0074] The impregnation treatment is specifically as follows: adding the mixture that has undergone the first carbonization treatment into asphalt and impregnating it at 300°C and 1.8Mpa for 4 hours;

[0075] The second carbonization is as follows: the impregnated mixture is kept at 1250°C for 60 hours under an argon atmosphere;

[0076] The graphitization treatment is specifically as follows: graphitization treatment is performed at 2200° C. for 4 h in an argon atmosphere.

[0077] Example 2

[0078] The present invention provides a method for preparing an oxidation-resistant graphite material, comprising the following steps:

[0079] S1, mixing asphalt coke, coal tar pitch and boron-containing solvent to obtain a mixture;

[0080] S2, cooling the mixture after hot kneading and crushing;

[0081] S3, subjecting the crushed mixed material to cold isostatic pressing;

[0082] S4, subjecting the cold isostatic pressing treated mixed material to a first carbonization treatment;

[0083] S5, adding the mixture that has undergone the first carbonization treatment into the melted asphalt for impregnation treatment;

[0084] S6, subjecting the impregnated mixture to a second carbonization treatment;

[0085] S7, graphitizing the mixture that has undergone the second carbonization treatment;

[0086] Wherein, the boron-containing solvent is triethyl borate;

[0087] The particle size of pitch coke is 20 μm;

[0088] In the step of mixing asphalt coke, coal tar pitch and boron-containing solvent, the mass of coal tar pitch is 30% of the mass of asphalt coke, and the mass ratio of boron-containing solvent to asphalt is 1:99;

[0089] The mixture was kneaded at 220°C for 3 h, cooled, and crushed to an average particle size of 70 μm.

[0090] The process parameters of cold isostatic pressing are: pressure 130Mpa, time 2h;

[0091] The first carbonization treatment is as follows: the cold isostatically pressed mixture is kept at 1250°C for 50 h under an argon atmosphere;

[0092] The impregnation treatment is specifically as follows: adding the mixture that has undergone the first carbonization treatment into asphalt and impregnating it at 300°C and 1.8Mpa for 4 hours;

[0093] The second carbonization is as follows: the impregnated mixture is kept at 1250°C for 60 hours under an argon atmosphere;

[0094] The graphitization treatment is specifically as follows: graphitization treatment is performed at 2200° C. for 4 h in an argon atmosphere.

[0095] Example 3

[0096] The present invention provides a method for preparing an oxidation-resistant graphite material, comprising the following steps:

[0097] S1, mixing asphalt coke, coal tar pitch and boron-containing solvent to obtain a mixture;

[0098] S2, cooling the mixture after hot kneading and crushing;

[0099] S3, subjecting the crushed mixed material to cold isostatic pressing;

[0100] S4, subjecting the cold isostatic pressing treated mixed material to a first carbonization treatment;

[0101] S5, adding the mixture that has undergone the first carbonization treatment into the melted asphalt for impregnation treatment;

[0102] S6, subjecting the impregnated mixture to a second carbonization treatment;

[0103] S7, graphitizing the mixture that has undergone the second carbonization treatment;

[0104] Wherein, the boron-containing solvent is methyl borate;

[0105] The particle size of pitch coke is 20 μm;

[0106] In the step of mixing asphalt coke, coal tar pitch and boron-containing solvent, the mass of coal tar pitch is 30% of the mass of asphalt coke, and the mass ratio of boron-containing solvent to asphalt is 3:97;

[0107] The mixture was kneaded at 220°C for 3 h, cooled, and crushed to an average particle size of 70 μm.

[0108] The process parameters of cold isostatic pressing are: pressure 130Mpa, time 2h;

[0109] The first carbonization treatment is as follows: the cold isostatically pressed mixture is kept at 1250°C for 50 h under an argon atmosphere;

[0110] The impregnation treatment is specifically as follows: adding the mixture that has undergone the first carbonization treatment into asphalt and impregnating it at 300°C and 1.8Mpa for 4 hours;

[0111] The second carbonization is as follows: the impregnated mixture is kept at 1250°C for 60 hours under an argon atmosphere;

[0112] The graphitization treatment is specifically as follows: graphitization treatment is performed at 2200° C. for 4 h in an argon atmosphere.

[0113] Comparative Example 1

[0114] The comparative example provides a method for preparing a graphite material, comprising the following steps:

[0115] S1, mixing asphalt coke and coal tar to obtain a mixture;

[0116] S2, cooling the mixture after hot kneading and crushing;

[0117] S3, subjecting the crushed mixed material to cold isostatic pressing;

[0118] S4, subjecting the cold isostatic pressing treated mixed material to a first carbonization treatment;

[0119] S5, adding the mixture that has undergone the first carbonization treatment into the melted asphalt for impregnation treatment;

[0120] S6, subjecting the impregnated mixture to a second carbonization treatment;

[0121] S7, graphitizing the mixture that has undergone the second carbonization treatment;

[0122] The particle size of pitch coke is 20 μm;

[0123] In the step of mixing the asphalt coke and the coal tar pitch, the mass of the coal tar pitch is 30% of the mass of the asphalt coke;

[0124] The mixture was kneaded at 220°C for 3 h, cooled, and crushed to an average particle size of 70 μm.

[0125] The process parameters of cold isostatic pressing are: pressure 130Mpa, time 2h;

[0126] The first carbonization treatment is as follows: the cold isostatically pressed mixture is kept at 1250°C for 50 h under an argon atmosphere;

[0127] The impregnation treatment is specifically as follows: adding the mixture that has undergone the first carbonization treatment into asphalt and impregnating it at 300°C and 1.8Mpa for 4 hours;

[0128] The second carbonization is as follows: the impregnated mixture is kept at 1250°C for 60 hours under an argon atmosphere;

[0129] The graphitization treatment is specifically as follows: graphitization treatment is performed at 2200° C. for 4 h in an argon atmosphere.

[0130] Performance Testing

[0131] The graphitization degree and weight loss rate of the graphite materials in Examples 1 to 3 and Comparative Example 1 were tested. The graphitization degree was measured by XRD to determine the interplanar spacing of the graphite (002) crystal plane, and the formula The weight loss rate is calculated as follows: 1 g of the graphite materials in Examples 1 to 3 and Comparative Example 1 is oxidized in air at 600° C. for 30 h, and the mass of the remaining graphite material after oxidation is measured, thereby calculating the mass of the graphite material that has lost weight (i.e., the mass of the graphite material that has lost weight = 1-the mass of the remaining graphite material), and the weight loss rate = the mass of the graphite material that has lost weight / initial graphite material (1 g) × 100%.

[0132] The lattice parameters (c) and degree of graphitization (DOG) of the graphite materials in Examples 1 to 3 and Comparative Example 1 are shown in Table 1 below.

[0133] Table 1- Lattice parameters (c) and degree of graphitization (DOG) of graphite materials

[0134] d002 lattice parameter (c / A) Graphitization degree Example 1 3.369208 82.316 Example 2 3.368232 83.451 Example 3 3.366665 85.273 Comparative Example 1 3.371027 80.201

[0135] Figure 1 The XRD pattern of the graphite material prepared in Example 1.

[0136] Figure 2 This is the XRD pattern of the graphite material prepared in Example 2.

[0137] Figure 3 This is the XRD pattern of the graphite material prepared in Example 3.

[0138] Figure 4 This is the XRD pattern of the graphite material prepared in Comparative Example 1.

[0139] In Comparative Example 1, no boron-containing solvent was added, and the graphitization degree of the prepared graphite material was 80.201%, and the weight loss rate after oxidation in air at 600° C. for 30 h was 5.8%.

[0140] In Example 1, triisopropyl borate, a boron-containing solvent, was added to prepare an oxidation-resistant graphite material with a graphitization degree of 82.316% and a weight loss rate of 5.3% after oxidation in air at 600° C. for 30 h.

[0141] In Example 2, triethyl borate, a boron-containing solvent, was added to prepare an oxidation-resistant graphite material with a graphitization degree of 83.451% and a weight loss rate of 5.1% after oxidation in air at 600° C. for 30 h.

[0142] In Example 3, the boron-containing solvent methyl borate was added, and the graphitization degree of the prepared anti-oxidation graphite material was 85.273%, and the weight loss rate after oxidation in air at 600° C. for 30 hours was 4.7%. The graphitization degree and oxidation resistance of the anti-oxidation graphite material were improved.

[0143] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing an oxidation-resistant graphite material, characterized in that: The following steps are involved: Mixing asphalt coke or petroleum coke, coal tar, and a boron-containing solvent to obtain a mixture; The mixture is kneaded hot, cooled, and crushed; The crushed mixture is subjected to cold isostatic pressing; The cold isostatically pressed mixed material is subjected to a first carbonization treatment; The mixture that has undergone the first carbonization treatment is added into the melted asphalt for impregnation treatment; Carrying out a second carbonization treatment on the impregnated mixture; The mixed material subjected to the second carbonization treatment is graphitized; Wherein, the boron-containing solvent is an ester compound containing boron element.

2. The method for preparing the oxidation-resistant graphite material according to claim 1, characterized in that: The boron-containing solvent includes at least one of triisopropyl borate, triethyl borate and methyl borate.

3. The method for preparing the oxidation-resistant graphite material according to claim 1, characterized in that: The particle size of the asphalt coke or petroleum coke is 3 to 30 μm; And / or, in the step of mixing asphalt coke or petroleum coke, coal tar pitch and boron-containing solvent, the mass of coal tar pitch is 25% to 35% of the mass of asphalt coke or petroleum coke, and the mass of boron-containing solvent is 0.5 to 10% of the mass of coal tar pitch.

4. The method for preparing the oxidation-resistant graphite material according to claim 1, characterized in that: The mixture is kneaded at 200-250°C for 3-5 hours, cooled, and crushed to an average particle size of 60-80 μm.

5. The method for preparing the oxidation-resistant graphite material according to claim 1, characterized in that: The crushed mixture is subjected to cold isostatic pressing, wherein the process parameters of the cold isostatic pressing are: pressure of 120-140 MPa and time of 0.5-4 h.

6. The method for preparing the oxidation-resistant graphite material according to claim 1, characterized in that: The cold isostatically pressed mixture is subjected to a first carbonization treatment, wherein the first carbonization treatment specifically comprises: keeping the cold isostatically pressed mixture at 1200-1300° C. for 20-100 hours under an inert atmosphere.

7. The method for preparing the oxidation-resistant graphite material according to claim 1, characterized in that: The mixture that has undergone the first carbonization treatment is added to the melted asphalt for an impregnation treatment step; the impregnation treatment is specifically, adding the mixture that has undergone the first carbonization treatment to the asphalt and impregnating it at 280-320° C. and 1.5-2 MPa for 2-6 hours.

8. The method for preparing the oxidation-resistant graphite material according to any one of claims 1 to 7, characterized in that: In the step of subjecting the impregnated mixture to a second carbonization treatment, the second carbonization treatment specifically comprises: keeping the impregnated mixture at 1200-1300° C. for 20-100 hours under an inert atmosphere; The inert atmosphere includes at least one of nitrogen, helium, neon and argon.

9. The method for preparing the oxidation-resistant graphite material according to claim 1, characterized in that: The graphitization treatment is specifically as follows: graphitization treatment is carried out at 2000-2400° C. for 3-5 hours under an inert atmosphere.

10. An oxidation-resistant graphite material, characterized in that: The preparation method is as described in any one of claims 1 to 9.

Citation Information

Cited By

  • Carbon graphite material as well as preparation method and application thereof

    CN121573987A

  • High temperature heat treatment and densification process of high strength isostatic pressed graphite

    CN122705299A